A qualitative investigation of mental health in women of refugee background resettled in Tasmania, Australia - Clare Hawkes; Kimberley Norris; Janine Joyce; Douglas Paton (BMC, 2021)
Abstract Background Women of Refugee Background (WoRB) are a highly vulnerable population with complex going mental health needs following resettlement. In Australia, there has been a substantial increase in WoRB being resettled in rural and regional locations. Despite this, no research to date has specifically focused on factors contributing to mental distress in WoRB in regional resettlement locations. The current study aimed to address this gap in literature. Methods 21 semi-structured qualitative interviews were conducted with WoRB and service providers in regional locations of Tasmania, Australia. Interviews were audio recorded and transcribed verbatim. Transcripts were analysed utilising Braun and Clarke (Qual Res Psychol 3(2):77-101, 2006) framework for conducting thematic analysis. Results Thematic analysis revealed that WoRB conceptualised mental health as a pathogenic entity, which significantly influenced their mental health help-seeking behaviours. The findings also highlighted how resettlement to a rural and regional location of Australia may exacerbate many of the factors which contribute to ongoing mental distress in WoRB. Conclusions The findings of the current study build upon existing research which indicates the adverse impacts post-migrations stressors can have on the mental health of individuals of refugee background. Furthermore, this study suggests that the current services and supports available to WoRB resettled in regional locations of Australia are inadequate, and under-resources. These findings are discussed in regard to practical and policy implications which should be addressed to better support the mental health of WoRB resettled in rural and regional locations of Australia.